Influence of combusting methane-hydrogen mixtures on compression–ignition engine exhaust emissions and in-cylinder gas composition. (26th January 2017) - Talibi, Midhat; Balachandran, Ramanarayanan; Ladommatos, Nicos
Abstract: The paper presents an experimental investigation of combusting methane-hydrogen mixtures, pilot-ignited by diesel fuel, on a naturally aspirated, direct injection compression ignition engine. The tests were performed with two diesel fuel flow rates for pilot-ignition, and the engine was supplied with different quantities of methane-hydrogen mixtures (in various proportions) to vary the engine load between 0 and 7 bar IMEP. In addition, engine in-cylinder gas samples were collected with two geometric sampling arrangements and at various instants during the engine cycle, to measure species concentrations within the engine cylinder. The results showed lower exhaust CO2 and particulate emissions at all engine loads when combusting methane-hydrogen mixtures as compared to diesel fuel only. CO and unburned THC emissions were higher for methane-hydrogen mixtures at all engine loads when compared with diesel fuel only. NOx emissions increased with increasing proportion of hydrogen in the aspirated mixture at all engine loads. In-cylinder NOx levels were observed to be higher in the region between the fuel sprays as compared to within the spray core, attributable to higher temperatures reached in between the sprays post ignition. Highlights: Effects of diesel fuel pilot ignited methane-hydrogen mixtures on exhaust emissions were investigated. Temporally resolved in-cylinder gas sampling gave further insight into emissions variation during the engine cycle. NOx emissions increased with increasing proportion of hydrogen in the aspirated mixture. Particulate emissions significantly decreased when diesel fuel was replaced by CH4 –H2 mixtures at all engine loads. In-cylinder NOx levels were higher between diesel fuel sprays relative to within the spray core.